2020
DOI: 10.1155/2020/7130105
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Molecular Targets of the Tao‐Hong‐Si‐Wu‐Tang Formula for Treatment of Osteonecrosis of Femoral Head: A Network Pharmacology Study

Abstract: The Tao-Hong-Si-Wu-Tang (THSWT) formula, a classic prescription of traditional Chinese medicine, has long been used for the treatment of osteonecrosis of femoral head (ONFH). However, its mechanisms of action and molecular targets are not comprehensively clear. In the present study, the Traditional Chinese Medicine System Pharmacology (TCMSP) database was employed to retrieve the active compounds of each herb included in the THSWT formula. After identifying the drug targets of active compounds and disease targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Quercetin inhibits LPS-induced osteoblast apoptosis, promotes BMSC proliferation, enhances osteoblast differentiation through the MAPK signaling pathway [21][22][23] . Studies have shown that luteolin can exert anti-apoptotic effects through mitochondrial pathways in osteoblasts [24] , and luteolin has been found to have strong anti-inflammatory effects and help inhibit bone resorption induced by mature osteoclasts [25][26][27] . Kaempferol inhibits osteoclasts and promotes osteoblast differentiation [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin inhibits LPS-induced osteoblast apoptosis, promotes BMSC proliferation, enhances osteoblast differentiation through the MAPK signaling pathway [21][22][23] . Studies have shown that luteolin can exert anti-apoptotic effects through mitochondrial pathways in osteoblasts [24] , and luteolin has been found to have strong anti-inflammatory effects and help inhibit bone resorption induced by mature osteoclasts [25][26][27] . Kaempferol inhibits osteoclasts and promotes osteoblast differentiation [28] .…”
Section: Discussionmentioning
confidence: 99%
“…It is gradually accepted in clinical applications and medical institutes worldwide [7][8][9][10]. Numerous basic and clinical experiments show that compound TCM is economical and has multiplicity and low side effects in treating SANFH [10,11]. Gujiansan is a formula created by Professor Wei Guikang, a master of TCM, based on the theory of traditional Chinese therapeutics and medication as well as his accumulated experience in the past decades.…”
Section: Introductionmentioning
confidence: 99%